2016
DOI: 10.1111/ejss.12350
|View full text |Cite
|
Sign up to set email alerts
|

The North Wyke Farm Platform: effect of temperate grassland farming systems on soil moisture contents, runoff and associated water quality dynamics

Abstract: SummaryThe North Wyke Farm Platform was established as a United Kingdom national capability for collaborative research, training and knowledge exchange in agro‐environmental sciences. Its remit is to research agricultural productivity and ecosystem responses to different management practices for beef and sheep production in lowland grasslands. A system based on permanent pasture was implemented on three 21‐ha farmlets to obtain baseline data on hydrology, nutrient cycling and productivity for 2 years. Since th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
83
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 23 publications
0
83
0
Order By: Relevance
“…As demonstrated here, it is possible to utilize existing datasets (from unrelated experiments carried out under similar environments) and create "hypothetical supply chains" that are sufficiently realistic for exploratory purposes. However, as the degree of uncertainty surrounding this approach cannot be specified, ideally a better way forward to overcome this issue would be to employ a whole supply chain approach (Orr et al, 2016), whereby actual products originating from different on-farm treatments are marked and tracked along the marketing process and used for quality evaluation and consumer trials. The finding from the present study, namely that nutritional quality rather than quantity is likely to play a key role in sustainable livestock production, warrants future studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“…As demonstrated here, it is possible to utilize existing datasets (from unrelated experiments carried out under similar environments) and create "hypothetical supply chains" that are sufficiently realistic for exploratory purposes. However, as the degree of uncertainty surrounding this approach cannot be specified, ideally a better way forward to overcome this issue would be to employ a whole supply chain approach (Orr et al, 2016), whereby actual products originating from different on-farm treatments are marked and tracked along the marketing process and used for quality evaluation and consumer trials. The finding from the present study, namely that nutritional quality rather than quantity is likely to play a key role in sustainable livestock production, warrants future studies in this area.…”
Section: Discussionmentioning
confidence: 99%
“…All inputs and losses are measured, including losses of P in surface and subsurface drainage. Full details of this complicated experiment are given in Orr et al (2016). Reporting some of the early findings from this experiment, Peukert et al (2014) found that in these conventional grassland systems, suspended sediment and total P concentrations in run‐off often exceeded water quality limits recommended by the European Freshwater Fisheries Directive (25 mg total P L −1 ) and the European Water Framework Directive (0.04 mg soluble reactive P L −1 ) (UK TAG, 2008).…”
Section: Environmental Issues: Phosphorus and Eutrophicationmentioning
confidence: 99%
“…Thus changing climate, with important, potential implications for rainfall patterns and hydrochemical responses in rivers, is adding a new urgency to understanding and managing the issue of excess nitrate in our agricultural-dominated landscapes (Howarth et al, 2012). In the UK, there is concern that warmer, drier summers and wetter winters may lead to increased nitrate export from lowland catchments (Whitehead et al, 2009), one scenario being an increased accumulation of nitrate in soils by mineralization in hot, dry summers followed by flushing of nitrate from soils during autumn at the end of the drought (Whitehead et al, 2006) especially in conjunction with first-flush responses (Jiang et al, 2010;Yang et al, 2015;Orr et al, 2016). However, considerable uncertainty exists around current predictions (Heathwaite, 2010), and policymakers lack results from studies at appropriate temporal and spatial scales for confident decision making (Watts et al, 2015).…”
Section: Introductionmentioning
confidence: 99%